RESEARCH ON ACCELERATING PARTICIPATION OF TRADITIONAL CHINESE MEDICINE SERVICE TRADE IN THE BELT AND ROAD INITIATIVE - Xu Haiqing; Li Tingting; Huo Wentao; Cao Rong, (Journal of Business and Innovation (Бизнес & Инноваци), 2023)
With the advancement of Trade in the Belt and Road initiative, the international recognition of Traditional Chinese Medicine(TCM) has been continuously enhanced. By analyzing the current situation and existing problems of TCM service trade, the author puts forward some suggestions on the development of the service trade of Chinese medicine, improving the industrialization level and creating a Chinese traditional Chinese medicine brand with international influence, accelerating the development of international standardization and regulations and breaking through barriers to trade in TCM technologies making full use of the influence of traditional cultural resources to promote the development of TCM service trade implementing a diversified model of TCM service trade to showcase the characteristics of TCM services paying attention to the training of qualified personnel.